2022
DOI: 10.1101/2022.01.05.475040
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Humanization of wildlife gut microbiota in urban environments

Abstract: Urbanization is rapidly altering Earth’s environments, demanding investigations of the impacts on resident wildlife. Here, we show that urban populations of coyotes (Canis latrans) and crested anole lizards (Anolis cristatellus) acquire gut microbiota constituents found in humans, including the gut bacterial lineages most significantly associated with urbanization in humans (e.g., Bacteroides). Comparisons of urban and rural wildlife and human populations revealed significant convergence of the gut microbiota … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The transmitted microbes found in the above were all within the range of these 118 intersecting genera, and they had variable effects on the physiological and biochemical activities of the body. Previous studies have also indicated that transmission of the gut microbiota can occur between humans and mammalian when they come into close contact, such as predator-prey interactions (22). In short, we speculated that camel milk can act as a vehicle to deliver natural microflora to colonize and function in the gut of the recipient.…”
Section: Staphylococcusmentioning
confidence: 86%
“…The transmitted microbes found in the above were all within the range of these 118 intersecting genera, and they had variable effects on the physiological and biochemical activities of the body. Previous studies have also indicated that transmission of the gut microbiota can occur between humans and mammalian when they come into close contact, such as predator-prey interactions (22). In short, we speculated that camel milk can act as a vehicle to deliver natural microflora to colonize and function in the gut of the recipient.…”
Section: Staphylococcusmentioning
confidence: 86%
“…Anthropogenic disturbances are known to heavily impact wildlife populations in a plethora of forms, including changes in host microbiomes (Zhu et al., 2021). Disruptions in the gut microbiome composition have been demonstrated, including the domestication and “humanization” of the wildlife gut microbiome (Dillard et al., 2022; Prabhu et al., 2020), and the shift in the microbiota community composition due to an increase in disease‐associated taxa and a decrease of beneficial bacteria (Wasimuddin et al., 2022). On top of that, population bottlenecks lead to the loss of genetic variation, increased inbreeding and therefore, resulting in a less diverse microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Anthropogenic disturbances are known to heavily impact wildlife populations in a plethora of forms, including changes in host microbiomes (Zhu et al, 2021). Disruptions in the gut microbiome composition have been demonstrated, including the domestication and 'humanization' of the wildlife gut microbiome (Dillard et al, 2022;Prabhu et al, 2020), and the shift in the microbiota community composition due to an increase in disease-associated taxa and a decrease of bene cial bacteria (Wasimuddin et al, 2022). On top of that, population bottlenecks lead to the loss of genetic variation, increased inbreeding and therefore, resulting in a less diverse microbiome.…”
Section: Discussionmentioning
confidence: 99%